Extent and causes of the collapse in the registration of innovative medications in Lebanon: A mixed-methods analysis - Wadih Mina; Hanadi Nahas; Maria Rita Lteif; Rita Karam; Fadi El-Jardali; Louis Garrison; Soumana C. Nasser (PLoS ONE, 2025)
Objectives Delays in innovative drug registration across countries, or the “drug approval lag”, can cause inequities in treatment access, thereby worsening patient outcomes. Registration delays hinder the first step in making treatments available, and are often linked to regulatory inefficiencies, constrained healthcare financing, and fragmented decision-making. Since late 2019, Lebanon’s health system has faced overlapping socioeconomic and political crises, yet their impact on innovative medication registration remains undocumented. This study aimed to measure this impact by comparing Lebanon’s drug approval lag before (2014–2019) and after (2020–2024) the crisis and to develop an interpretive framework exploring the rationale behind an informal policy to delay innovative medication registration. Methods A mixed-methods approach was adopted. Innovative medications approved by the Food and Drug Administration (FDA) or the European Medicines Agency (EMA) between 2014 and 2024 were included and compared to local registration timelines in Lebanon. In-depth interviews with policymakers, industry leaders, and healthcare providers informed the interpretive framework. Results Findings revealed a dramatic fall in innovative medication registrations post-crisis over these two periods. The proportion of FDA-approved innovative medications registered in Lebanon dropped from 43.6% to 0% and EMA-approved medications dropped from 59.4% to 0%. Pre-crisis, average registration time was under two years; post-crisis, delays are estimated to exceed four years. Our interpretive framework suggests the intermediate effects of delaying innovative medication registration are mainly to control costs and reduce reimbursement pressures on the Ministry of Public Health. However, key stakeholders believe the resulting negative consequences, such as reduced access to life-saving treatments and greater dependence on parallel market importation, outweigh the short-term benefits. Conclusion Health systems are complex adaptive systems, where policies affecting innovative drug approvals may not only delay access, but also trigger unintended consequences. In Lebanon, the registration of innovative medications should remain independent from reimbursement decisions and grounded in evidence-informed health policies.